Crystal-associated cholangiopathy in sheep grazing Brachiaria decumbens containing the saponin protodioscin - Brum,Karine B. (2007)
An outbreak of hepatogenous photosensitization is reported in a flock of 28 sheep grazing Brachiaria decumbens in Mato Grosso do Sul State, Central-Western Brazil. Seven lambs and an adult sheep were affected and 6 of them died. Two surviving affected lambs and one lamb without clinical signs had increased serum values of gamma glutamyltransferase, bilirubin, and cholesterol. In two adult unaffected sheep those parameters were within normal values. An adult sheep submitted to necropsy presented moderate body condition, unilateral corneal opacity, drying of the muzzle, moderate jaundice, increased lobular pattern of the liver, and a distended gallbladder. Histological lesions were epithelial degeneration, necrosis, and hyperplasia of small bile ducts. Mild amounts of foamy macrophages were observed, mainly in the centroacinar zone. Diffuse swelling and vacuolation were observed in hepatocytes. Crystal negative images were found within bile ducts, foamy macrophages, and the lumen of some renal tubules. The heart showed multifocal areas of degeneration and necrosis of the muscle fibers. Pasture samples (Brachiaria decumbens) contained 2.36% of protodioscin. No Pithomyces chartarum spores were found in the pasture. Samples from a similar neighboring B. decumbens pasture grazed by cattle without photosensitization contained 1.63% of protodioscin isomers. Outbreaks of photosensitization caused by Brachiaria spp. are common in cattle in the Brazilian Cerrado (savanna) with about 51 million hectares of Brachiaria spp pastures. Sheep farming has been recently developed in this region, and the number of sheep is increasing significantly. Because sheep are more susceptible than cattle to lithogenic saponins, poisoning by Brachiaria should be an important limiting factor for the sheep industry.